A review on semitransparent solar cells for agricultural application. (December 2021) - Zhao, Yepin; Zhu, Yuan; Cheng, Hao-Wen; Zheng, Ran; Meng, Dong; Yang, Yang
Abstract: Modern agriculture dramatically increases food production and continuously plays a critical role to remit the food crisis in the world. However, agricultural modernization also consumes more energy and land than the traditional small-scale peasant farming. The integration of photovoltaics into modern agriculture is a promising method to utilize the vast agricultural land efficiently and provide extra energy for crop production. Due to the tunable energy of the organic molecules, semitransparent organic solar cell serves as an ideal candidate. Rationally designed devices can allow sunlight with selected wavelengths to pass though and get absorbed by the plants for photosynthesis. Meanwhile, relatively high photovoltaic performances are also preferred for energy generation. In this article, important studies of semitransparent organic solar cells for agricultural applications are reviewed, and the design routes and strategies are summarized. The perspectives for the future research on agricultural photovoltaics are also presented. Graphical abstract: Image 1 Highlights: Special requirements of organic photovoltaics (OPVs) for agricultural application and the challenges were introduced. Bringing from the experiences of traditional OPVs, potential methods for the enhancement of efficiency and transmittance were summarized. Outlooks and potential directions for future research on agricultural photovoltaics were presented.